GESTIÓN DEL TALENTO HUMANO PARA LA COOPERATIVA DE AHORRO Y CRÉDITO CACPE ZAMORA LTDA. EN LA OFICINA MATRIZ, UBICADA EN LA CIUDAD DE ZAMORA CANTÓN ZAMORA, PROVINCIA DE ZAMORA CHINCHIPE - Imacaña Gaona, Jorge David (2016)
This research work has the general objective to perform a "Proposal for Improving the Model of Human Resource Management for the credit union" CACPE ZAMORA "Ltda." That can generate an efficient administration in the institution. To meet this objective it was necessary the use of deductive, inductive, analytical methods and techniques of observation and the interview was applied to the manager and employee surveys working in the credit union Small Business CACPE Zamora Ltda. In the results begins with a historical overview of the company, then as part of diagnosis comprise the results of the interview and surveys the manager and employees of the cooperative, the department of human talent does not have the necessary updated strategies on the right management and staff development also not performed a correct selection and recruitment of personnel, we can say that the Human Resource management in its evolutionary context should apply proper management model to improve the selection process, effectiveness for compliance objectives and across various challenges. It is disclosed structured flowcharts, which consist charges are based on the current reality of the company, then in the Manual Functions valuable and important information is presented with respect to each of the charges that make up the cooperative functions and responsibilities of each of the members of the cooperative, avoiding duplication of functions and allowing better organization in the cooperative. the rules for admission and employment, it will allow the cooperative to select the most suitable for any office where a vacancy arises in the future staff developed. In addition the valuation of positions, where the system was applied on points with their respective stages from defining factors to the valuation of jobs was developed. To end the Manual Welcome to personnel entering the cooperative and manual functions where valuable and important information is presented with respect to each of the 6 charges that make up the cooperative, roles and responsibilities of each performed members of the cooperative, avoiding duplication of functions and allowing better organization in the cooperative. In addition the valuation of positions, where the system was applied on points with their respective stages from defining factors to the valuation of jobs, where the following results were obtained was developed. The total points as the valuation is 5410.00 salaries paid to employees of the company amounts to $ 10549.50 these data the straight line equation was applied, which resulted in a slope of 1.97 based on the value above the salary adjustment with recovery factor of 1.95 in order to determine the new salaries was made. The revaluation is only performed to the charges that were below the line of the salary adjustment, which in total amounted to 11: Accounting Assistant, Secretary, credit counselor, assistant file 1, matrix cashier, parent cashier, service Client 1 customer service 2 customer service advisor, matrix guard, guard matrix. Finalizing this point the rules of admission and employment was made, it will allow the cooperative to select the most suitable for any office where a vacancy arises in the future staff. Once the work completed it was determined the conclusions and recommendations being the most relevant to the selection of personnel for the credit union Small Business CACPE Zamora Ltda., Is not done according to established policies, which causes no staff suitable for different positions that owns the cooperative and within the recommendations suggest considering Function Manual, Rules of Admission and Employment and Job evaluation points, in order to assess systematically the performance of staff is hired in office, which it will determine whether it meets the requirements that are required for different positions of the credit union.